Friends with Benefits: The Evolved Psychology of Same- and Opposite-Sex Friendship - Lewis, David M.G.; Conroy-Beam, Daniel; Al-Shawaf, Laith; Raja, Annia; DeKay, Todd; Buss, David M. (Evolutionary psychology, 2011)
During human evolution, men and women faced distinct adaptive problems, including pregnancy, hunting, childcare, and warfare. Due to these sex-linked adaptive problems, natural selection would have favored psychological mechanisms that oriented men and women toward forming friendships with individuals possessing characteristics valuable for solving these problems. The current study explored sex-differentiated friend preferences and the psychological design features of same- and opposite-sex friendship in two tasks. In Task 1, participants (N = 121) categorized their same-sex friends (SSFs) and opposite-sex friends (OSFs) according to the functions these friends serve in their lives. In Task 2, participants designed their ideal SSFs and OSFs using limited budgets that forced them to make trade-offs between the characteristics they desire in their friends. In Task 1, men, more than women, reported maintaining SSFs for functions related to athleticism and status enhancement and OSFs for mating opportunities. In Task 2, both sexes prioritized agreeableness and dependability in their ideal SSFs, but men prioritized physical attractiveness in their OSFs, whereas women prioritized economic resources and physical prowess. These findings suggest that friend preferences may have evolved to solve ancestrally sex-linked adaptive problems, and that opposite-sex friendship may directly or indirectly serve mating functions.